Uso de las aulas virtuales en la asignatura de estudios sociales y su incidencia en el rendimiento académico en los estudiantes del 8vo año de EGB en la unidad educativa intercultural bilingüe “Shiry Cacha” - Janeth Roció Romero Salazar , María Eugenia Solís (2021)
ABSTRACT Teaching through technological resources and platforms is becoming more relevant every day and arouses the interest of the scientific community due to its ability to improve access to education and enable up-to-date instruction. In the last decade, virtual classrooms have been, par excellence, the environment where the teacher has been able to carry out the teaching process efficiently. The objective of this research is to determine the incidence of the use of the virtual classroom on academic performance in the Social Studies subject of the eighth year of EGB in the UEIB “Shiry Cacha” during the period September 2020 - June 2021. For which it is described how the students used the virtual classroom in the subject; Its use and the academic performance of the students were compared and finally a virtual classroom was created for the teaching of coexistence as a curricular block of the subject. It was concluded that the virtual classroom proved to be agile and with a large storage capacity; However, the students did not have instructions to use it, there was no information on the subject or on the teaching team, and significant deficits were observed in terms of the informative and evaluative dimension. From the analysis of the instruments, it was found that technological tools, technical skills, basic skills and the commitment and autonomy of students have a high positive correlation with academic performance. While the lowest correlation was identified in communication and perception. Keywords: Virtual classroom, academic performance, Social Studies